A experiência religiosa e o sentido da vida no pensamento de Viktor Emil Frankl - Nunes, Claudio Luis (2014)
Viktor Emil Frankl s thought (philosophy) concerning the meaning of life is relevant and pertinent, because there is still a universal clamor for this meaning, which is heard especially in urban areas where the masses are concentrated. It looks as though the larger the concentration of people, the greater the globalization of the world advances, the louder this cry for help is heard. This cry for a meaningful life is present both in the young as well as in older adults in all social classes. The world has lived through transformations and an existential vacuum is visible in the individual of today s society; the sensation of the lack of meaning, an interior emptiness. Beginning with this observation, this research has as its objective to demonstrate that it is possible to find meaning to life, having as a fundamental presupposition the discovery of the meaning of life by each person and the use of the cognitive power of the individual mind. It is only through this presupposition that it is possible to understand the reason why Frankl dedicated himself to the topic of the meaning of life emphasizing the role of faith, religiosity and logotherapy as the answer for the question about the meaning [of life] that has as its objective to widen the horizon of the human being, thus showing that, to all who can still be enthusiastic about something, there could still be much to do a significant number of tasks awaits them. Therefore, there is enough meaning.